Respon Morfologi dan Fisiologi Lima Varietas Padi pada Pemberian Pupuk Organik Diperkaya Mikroba - Adwiyani, Pustika; Sugiyanta; Maya Melati; Titi Candra Sunarti, (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Microbial enriched organic fertilizer as a source of soil organic matter plays a role in soil fertility and crop productivity. Various varieties have different responses to organic fertilization. This research was to determine the morphological and physiological responses of five rice varieties to microbial-enriched organic fertilizer treatments. The experiment was conducted from July 2020 to January 2021 at Sawah Baru Field, Faculty of Agriculture, IPB University. The experiment used a split-plot design with the main plot being four doses of microbial-enriched organic fertilizer, namely 0, 10, 20, and 30 tons ha-1 and the subplots were five rice varieties, namely IPB 3S, Inpari 24, Hipa 18, Inpari 32, and Tarabas. The results showed that microbial-enriched organic fertilizer application increased plant height, number of tillers, root dry weight, shoot dry weight, greenish of leaf, total grain content, and productive tillers. The application of organic fertilizer from 10 to 30 tons ha-1 resulted in higher dry grain yields per hectare than control by 12.91% to 32.5%. The application of microbial-enriched organic fertilizer up to 30 tons ha-1 still increase grain per hectare productivity, so the optimum dose of microbial-enriched organic fertilizer can not be determined yet.Keywords: greenish of leaf, hybrid, high yielding varieties, microbes, nutrient uptake